The Impact of Universal Health Coverage Implementation on the Increase in Patient Referrals at the Poso Regional General Hospital - Tri Budiono; Budiman Budiman; Finta Amalinda (Journal of Public Health Indonesian, 2026)
Universal Health Coverage (UHC) has transformed health service utilization patterns across Indonesia, particularly through the Jaminan Kesehatan Nasional (JKN) program administered by BPJS Kesehatan. This study examines the impact of UHC implementation on the increase in patient referrals at Poso Regional General Hospital (RSUD Poso), Central Sulawesi, Indonesia. Using a mixed-methods approach combining retrospective secondary data analysis and cross-sectional survey, data were collected from 2020 to 2024 covering 6,418 referral cases in 2024 alone. Results indicate a significant and progressive increase in patient referrals, from a rate of 12.0% in 2020 to 21.7% in 2024, representing a cumulative growth of approximately 190%. The proportion of JKN-based referrals rose from 73.6% to 89.2% over the same period. The most prevalent referral diagnoses involved cardiovascular diseases, neoplasms, and diabetes mellitus. Improvements in referral documentation compliance (67.3% to 88.2%) and reduced hospital waiting time (4.2 to 2.7 days) were also observed. These findings confirm that UHC implementation has substantially expanded access to higher-level hospital services at RSUD Poso, while simultaneously highlighting challenges of healthcare capacity management in remote areas. Strengthening primary care gatekeeping functions and expanding hospital capacity are recommended as key policy responses.